Improving Students' Reading Comprehension of Narrative Text Using Blooket - Pandunalbi Prakoso; Fajar Riyantika; Nita Sitta Rachma (U-Jet Unila Journal of English Language Teaching, 2026)
This study aimed to determine whether there was a significant improvement in ninth-grade students' reading comprehension of narrative texts at SMP Negeri 3 Pringsewu after being taught using Blooket. This study employed a quantitative approach using a one-group pre-test and post-test design. The sample consisted of 31 students selected through cluster random sampling. Data were collected through a 30-item multiple-choice reading test and were analyzed using a paired sample t-test in SPSS 26.0. The results showed that the t-value was higher than the t-table value (26.952 > 2.042) with a significance value of 0.000, which was lower than 0.05, indicating that the null hypothesis was rejected. The mean score increased from 58.92 in the pre-test to 82.47 in the post-test, with a gain of 23.55 points. The highest improvement was found in main idea (26.48%), while the lowest was in inference (15.53%). It can be concluded that Blooket significantly improved students' reading comprehension of narrative texts. Therefore, English teachers are encouraged to integrate Blooket as an alternative game-based learning medium to enhance students' reading comprehension of narrative texts and foster a more engaging classroom environment.